Adsorptive properties of Garcinia Mangostana Linn. based activated carbon - Wan Fadhilah Wan Mohd Khalik (School of Environmental Engineering, University Malaysia Perlis, 2012)
The adsorption of two different groups of dyes which were anionic (Acid Orange 7) and cationic (Methylene Blue) onto Garcinia Mangostana Linn.(GML) based activated carbon was studied for the removal of dyes from aqueous solutions. The operating variables studied were contact time, initial dyes concentration, particle size, adsorbent dosage and temperature. The experimental data were analyzed by using Langmuir and Freundlich which is models of adsorption. The physical and chemical characterization of GML was carried out through Fourier Transform Infrared (FTIR) Spectrometer and Scanning Electron Microscope (SEM). The adsorption rates for both dyes are almost same. Langmuir isotherm gives R2 for methylene blue is 0.999 and its maximum capacity is 125 mg/g, while for acid orange 7, the R2 value is 0.976 and its maximum capacity, qm is 1.055 mg/g. The R2 based on Freundlich isotherm for methylene blue and acid orange 7 is 0.947 and 0.896 respectively, while their adsorption capacity is 9.506 mg/g for methylene blue and 0.474 mg/g for acid orange 7.